Pengaruh pertumbuhan Aset, Leverage, ukuran perusahaan dan Profitabilitas terhadap kebijakan Dividen - Fatiyah, Riska Nurul; Purwaningsih, Eny (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The ideal dividend policy divides current payouts and long-term growth equally. Thus, the purpose of this research is to determine the impact of asset growth, leverage, firm size, and profitability on empirical dividend policy for companies in the food and beverage subsector listed on the Indonesia Stock Exchange, either partially or concurrently, during 2016 until 2020. This analysis uses the form comparative causal analysis to determine the relationship correlation two or many variables. Purposive sampling was used to choose manufacturers with in food and beverage subsector that were posted here on Indonesia Stock Exchange between 2016-2020 as samples for this study. Obtained 8 corporations which meet qualifications for the research sample, then the sample can be obtained 40 financial statements. This research method uses multiple regression analysis. The results partially prove that the profitability variable (NPM) on dividend policy has had a positive and significant effect, other variables of asset growth (AG) and leverage (DER) have a negative and significant effect on dividend policy, and firm size (SF) have had no effect on dividend policy. Simultaneously, there influence for the variables on asset growth (AG), leverage (DER), firm size (SF), and profitability (NPM) for dividend policy was obtained..